2021
DOI: 10.1152/jn.00145.2021
|View full text |Cite
|
Sign up to set email alerts
|

Motor skill training without online visual feedback enhances feedforward control

Abstract: Motor skill learning involves improvement in feedforward control, the ability to execute a motor plan more reliably, and feedback control, the ability to adjust the motor plan on the fly. The dependence between these control components and the association between training conditions and their improvement have not been directly examined. This study characterizes the contribution of feedforward and feedback control components to motor skill learning using the Arc Pointing Task (APT), a drawing task that requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 43 , 76 In direction learners, reinforcement of less variable trajectories that entered the target from the same direction could have led to learning of feedforward movement, relying less on moment-to-moment feedback. 2 , 6 As endpoint-biased mice learned the task, sensory error-based learning, 77 80 which has been shown to exist in mice, 51 , 72 may also have contributed to the refinement 81 , 82 in addition to learning from reinforcement. Endpoint learner animals may thus have improved error sensitivity as it has been reported that the movements made as corrections to sensory feedback errors can be a strong teaching signal that allows learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 , 76 In direction learners, reinforcement of less variable trajectories that entered the target from the same direction could have led to learning of feedforward movement, relying less on moment-to-moment feedback. 2 , 6 As endpoint-biased mice learned the task, sensory error-based learning, 77 80 which has been shown to exist in mice, 51 , 72 may also have contributed to the refinement 81 , 82 in addition to learning from reinforcement. Endpoint learner animals may thus have improved error sensitivity as it has been reported that the movements made as corrections to sensory feedback errors can be a strong teaching signal that allows learning.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy is to move in a certain direction for a set distance, as in a learned feedforward movement. 1 , 2 Another is to move so that the hand ends up in the learned target location, using the limb’s sensory state 3 , 4 to move by feedback. 5 , 6 The primary motor cortex is known to be crucial for targeted reaching movements across species.…”
Section: Introductionmentioning
confidence: 99%
“…Second, when reaching under mirror reversal condition, feedback control was not adaptively changed when participants were trained without online corrections [19,20]. Third, recent findings show that when people learn to produce a circle-shaped movement, improvements in feedforward and feedback do not always work in concert [22]. Indeed, although training without online feedback improved both feedforward and feedback control, training with online feedback benefited only to feedback control.…”
Section: Asymmetrical Transfer Between Reaching and Trackingmentioning
confidence: 95%
“…In the first one, training of reflex responses by means of short mechanical perturbations was shown to transfer to feedforward control of reaching [21]. In contrast, a recent study using an arc-pointing task under various conditions suggests that on-line feedback training could actually suppresses improvement in feedforward control during motor learning [22].…”
Section: Introductionmentioning
confidence: 96%